2003
DOI: 10.1159/000072692
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of an Aortic Anastomotic Aneurysm into a Ureter

Abstract: A case of rupture of a false aneurysm of the distal aorta into the left ureter is reported. The patient presented with purulent hydronephrosis and hematuria. A left aorto-femoral graft had been inserted 3 years earlier, which became infected and was then removed. After 2 years a false distal aortic aneurysm developed, and in the last 6 months recurrent episodes of hematuria have occurred. An aorto-ureteric fistula was confirmed at surgery, and a left nephrostomy was performed with proximal and distal ligation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Ureteroarterial fistula can be difficult to diagnose because it is very rare and the first symptom is often intermittent hematuria, which is routine symptom after urological surgery. [1][2][3][4][5] Only ureterography and selective iliac arteriography have been relatively successful in identifying the fistula; however, there are a few cases with sudden major bleeding such as in our patient. 4,[6][7][8] Keller et al 6 reported that 89% of patients with the correct diagnosis recovered and were discharged from the hospital; in contrast, there was a 52% mortality rate associated with an unsuspected or undiagnosed ureteroarterial fistula.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ureteroarterial fistula can be difficult to diagnose because it is very rare and the first symptom is often intermittent hematuria, which is routine symptom after urological surgery. [1][2][3][4][5] Only ureterography and selective iliac arteriography have been relatively successful in identifying the fistula; however, there are a few cases with sudden major bleeding such as in our patient. 4,[6][7][8] Keller et al 6 reported that 89% of patients with the correct diagnosis recovered and were discharged from the hospital; in contrast, there was a 52% mortality rate associated with an unsuspected or undiagnosed ureteroarterial fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Extra-anatomical arterial reconstruction and nephrectomy or nephrostomy were added if required. 2,3,5 Some authors recommend the use of transarterial embolization of the arteries with extra-anatomical bypass. 4,6 One of the most noteworthy postoperative complications of aortoureteric fistula is local infection, especially when artificial materials are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation